Funny channel gene mutations associated with arrhythmias. (17th April 2013) - DiFrancesco, Dario
Abstract : Abstract Many diverse data support a role of the funny current ( I f ) in pacemaking and heart rate control. Among them, clinically relevant applications have special impact, since they translate the concept of funny channel‐based pacemaking into practical developments of potential therapeutic value. For example, the I f role in pacemaking is the basis for a pharmacological approach to heart rate control. Ivabradine, a specific f‐channel blocker acting as a 'pure heart rate reducing' agent, is used today as a therapeutic tool in chronic stable angina and heart failure. Also, the pacemaking capability of funny channels has been the main rationale behind the development of 'biological' pacemakers, whose aim is to eventually replace the electronic pacemakers implanted today. Finally, the role of I f in pacemaking implies that dysfunctional funny channels can contribute to rhythm disorders. This consideration has led to the search for inheritable forms of cardiac arrhythmias potentially linked to functional changes of HCN4 channels, the molecular correlates of funny channels. This review addresses recent reports where investigation of families with arrhythmias has allowed the identification of specific HCN4 channel mutations associated with different types of rhythm disorders, specifically with sinus bradycardia. The perspective of future research in this field is also addressed.